Accelerated Shelf-life Testing of Balado Potato Chips Using Arrhenius Model Approach - Yusuf Irfan; Andini Putri Riandani; Anita Suri (Food Science and Technology Journal (Foodscitech), 2023)
Potatoes are a commodity that has the potential to be developed as a source of carbohydrates to support food diversification programs, increase farmer incomes, non-oil and gas export commodities, and processed industrial raw materials. One of the processed products from potatoes that are typical and popular with Indonesian people is balado potato chips. As a product that will ultimately be consumed, of course, the value of product safety (food safety) in the form of shelf life information needs to be considered. Product samples were incubated in an incubator with three different storage temperatures, namely 25°C, 30°C, and 45°C. Samples were analyzed with hedonic parameters, FFA levels, and water content every 7 days for 28 days (days 0, 7, 14, 21, and 28). The product shelf life at 25 °C, 30 °C and 45 °C respectively 37, 36 and 32 days. it is recommended that potato chip products be stored in closed packaging and stored in a cool place and avoid being stored in a place exposed to sunlight which will affect storage temperature and also free fatty acid levels which can cause rancidity.